anonymous
  • anonymous
Let T: R3 -> R4 be the linear transformation defined as follows:....? T(x,y,z) = (x-y+3z, -2x+2y-5z, 3x-3y+7z, -x+y+2z) 1. Find a formula for all elements in ker(T). 2. Is there an (x,y,z) in R3 so that T(x,y,z) = (1,-1,1,4)? (You do not need to find (x,y,z) if it exists, but explain how you know you answer is correct.) 3. Is there an (x,y,z) in R3 so that T(x,y,z) = (1,2,3,4)? (You do not need to find (x,y,z) if it exists, but explain how you know you answer is correct.)
Mathematics
  • Stacey Warren - Expert brainly.com
Hey! We 've verified this expert answer for you, click below to unlock the details :)
SOLVED
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.
jamiebookeater
  • jamiebookeater
I got my questions answered at brainly.com in under 10 minutes. Go to brainly.com now for free help!
anonymous
  • anonymous
1. The kernel of a transformation contains the vectors which T maps to (0,0,0,0). So to find ker(T) you should solve the following system of linear equations: \[\begin{array}{rl}x-y+3z=0&(I)\\-2x+2y-5z=0&(II)\\3x-3y+7z=0&(III)\\-x+y+2z=0&(IV)\end{array}\] From equations (I) and (IV) you immediately get that z must be zero which implies that x is equal to y. So \[\ker(T)=\{(t,t,0)\in\mathbb{R}^3\mid t\in\mathbb{R}\}.\] Well if you'd wanted to find (x,y,z) such that \[(x,y,z)\mapsto(1,-1,1,4)\] and \[(x,y,z)\mapsto(1,2,3,4)\] you'd have to solve \[\begin{array}{rl}x-y+3z=1&(I)\\-2x+2y-5z=-1&(II)\\3x-3y+7z=1&(III)\\-x+y+2z=4&(IV)\end{array}\] and \[\begin{array}{rl}x-y+3z=1&(I)\\-2x+2y-5z=2&(II)\\3x-3y+7z=3&(III)\\-x+y+2z=4&(IV)\end{array}\] If you're just interested in existence of solutions you should use Kronecker-Capelli theorem which claims that if the coefficient matrix \[A=\left[\begin{array}{ccc}1&-1&3\\-2&2&-5\\3&-3&7\\-1&1&2\end{array}\right]\] and the matrix extended by an extra column of the right-hand side (in our case (1,-1,1,4) and (1,2,3,4)) have the same rank then there is a solution. Let A|b denote the extended matrix. In exercise 2: rank(A)=2 and rank(A|b)=2 so there is a vector v (namely v=(-1,1,1)) such that T(v)=(1,-1,1,4). In exercise 3: rank(A) is still 2 but rank(A|b)=3 so there isn't a vector v=(x,y,z) such that T(v)=(1,2,3,4).

Looking for something else?

Not the answer you are looking for? Search for more explanations.